Mercury concentration in different tissues of Podocnemis unifilis (Troschel, 1848) (Podocnemididae: Testudines) from the lower Xingu River – Amazonian, Brazil - ARAUJO, Juliana de Souza (Universidade Federal do Pará, 2017)
Studies using chelonians as biosentinels of environment quality or health risks associated with turtle consumption are very rare, especially in the Amazon basin. This study aims to measure Mercury levels (Hg) in muscle, liver, fat and blood of Podocnemis unifilis from the lower Xingu River, assessing the possible difference in concentration between sexes and also evaluating the potential bioaccumulation along different body sizes. Samples were collected during the dry season (October 2012) and Mercury (Hg) concentrations were analysed by Cold Vapor Atomic Absorption Spectrometry (CVAAS). A total of 29 specimens of P. unifilis of different sizes showed low levels lower than 0.2 mg/Kg). Higher Hg concentrations were found in the liver, and significant correlations between Hg concentrations in the different tissues were also detected. There was no difference between males and females and a negative correlation was found between Hg concentration and body size.